Actitudes y percepciones del personal, y cuidado integral de personas adultas mayores, en el Hogar Santa Teresita Loja. - Quito Jiménez, Alicia Carlota (2013)
The elderly person requires care and attention. The issue revolves around COMPREHENSIVE CARE FOR OLDER PERSON, and its implications for their lives and in their relationship with carers. This research work was conducted at the Home St.Therese of the Child Jesus of Loja. The objective was to determine in what way the attitudes and perceptions of caregivers influence the comprehensive care of older people Hogar Santa Teresita del Niño Jesús de Loja, we conducted a descriptive study and interpretation that is to reach know the situations prevailing customs and attitudes through the exact description of the activities, objects, processes and people workin gin the Home In addition, a survey older people, and an interview with the home care staff. The survey sample consisted of 30 older people and 14 staff interviews caregiver with the following results Carers In addition, favorable criteria exist for older persons on the dealings with, 43.90 % as a result of the care they provide people working in the nursing home, despite the limitations found. KEYWORDS . Older Persons comprehensive care.